Preferences in data usage and the relation to the use of mobile applications - Mark de Reuver; Harry Bouwman (International Telecommunications Society (ITS), 2014)
While most user studies on mobile telecommunications focus on adoption of services, preferences in the use of data networks has hardly been studied. In this paper, we analyse data collected directly on smartphones to study preferences of users between cellular and WiFi networks. Moreover, we assess how the use of specific types of applications contributes to data consumption. In absolute terms, use of WiFi is higher than use of cellular networks. The spread among participants in use of cellular networks is very high, ranging from 0 to 100% of their total traffic. There are no significant differences between Apple and Android users. No effects were found of the size of the data plan on the amount of cellular data being consumed. Cellular network usage is especially driven by chat, social networking and browsing applications. High users of video applications do not significantly consume more bandwidth, which is at odds with conventional ideas on the capacity crunch. Log data on application usage explains data consumption better than self- -reported usage levels. The results are relevant for telecom operators to steer the amount of data being consumed over their cellular and WiFi networks. However, data consumption levels do differ greatly across the population, and as a large proportion of data traffic cannot be explained by application usage levels, preferences for data usage cannot be very well explained.
Keywords: 330; mobile services; mobile telecommunications; cellular networks; bandwidth; WiFi networks